Clinical and laboratory features associated with serum phosphate concentrations in malaria and other febrile illnesses - Suen, Ho-Ming E.; Pasvol, Geoffrey; Cunnington, Aubrey J. (Malaria journal, 2020)
Background Hypophosphatemia is common in severe infections including malaria. Previous studies suggested that serum phosphate concentrations correlate with temperature, but it is unclear whether the type of infection and other factors occurring during infection influence this association. Here relationships were investigated between serum phosphate levels, cause of fever, demographic, clinical and laboratory parameters. Methods Anonymized data were analysed from 633 adults with malaria or other febrile illness admitted to Northwick Park Hospital, London, UK. Univariable and multivariable generalized linear model analyses were performed to examine associations with serum phosphate levels. Interaction terms were included to investigate whether cause of fever (malaria vs other illness), malaria parasite species, or malaria severity influenced the association of other variables with phosphate. Results Hypophosphatemia was common in subjects with malaria (211/542 (39%)), and in other febrile illnesses (24/91 (26%)), however median phosphate levels did not differ significantly by diagnostic group, parasite species or severity of malaria. In all analyses, there were highly significant negative associations between serum phosphate and axillary temperature, and positive associations between serum phosphate and platelet count. There were no significant interactions between these variables and cause of fever, parasite species or severity of illness. Sodium and potassium concentrations were associated with serum phosphate in subjects with malaria and when data from all subjects was combined. Conclusion Serum phosphate is consistently associated with temperature and platelet count in adults with diverse causes of fever. This may be a consequence of phosphate shifts from plasma into cells to support ATP generation for thermogenesis and platelet activation.